The Urgency of Village-Level Mediators in Reducing Divorce Rates on North Central Java - Fadzlurrahman, Fadzlurrahman; A. Zaenurrosyid, A. Zaenurrosyid; Tali Tulab, Tali Tulab (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2025)
Marital issues are complex and, therefore, require careful handling to prevent divorce. This research explores effective strategies for managing household conflicts in Indonesia, particularly in the northern coastal regions of Java, with a focus on the role of Modin (religious community leaders) and the influence of customary law and positive law as mediation. The method used in this research is an empirical juridical approach, which includes the collection of primary and secondary data, case studies, interviews, and policy analysis. The results of the study show that while customary law has provided solutions to many societal issues, globalization and technology have encouraged communities to lean more on positive law in conflict resolution, even in traditional societies. The Modin plays a crucial role in mediating family conflicts and maintaining peace, while village heads often act as intermediaries in divorce cases, which can affect the village's reputation. The study recommends that villages, through the Modin, conduct mediation as an initial step in addressing household conflicts to prevent divorce and improve conflict-resolution outcomes.